Transactions on Engineering Technologies 25th World Congress on Engineering (WCE 2017) - Ao, Sio-Iong; Gelman, Len; Kim, Haeng Kon (Springer Nature Singapore : Imprint: Springer, 2019)
This volume contains a selection of revised and extended research articles written by prominent researchers participating in a large international conference on Advances in Engineering Technologies and Physical Science which was held in London, UK, 5-7 July, 2017. Topics covered include mechanical engineering, engineering mathematics, computer science, knowledge engineering, electrical engineering, wireless networks, and industrial applications. With contributions carefully chosen to represent the most cutting-edge research presented during the conference, the book offers the state of art in engineering technologies and physical science and applications, and also serves as an excellent reference work for researchers and graduate students working with/on engineering technologies and physical science and applications.